Guatemala : Technical Assistance Report-Statistics Technical Assistance and Training Evaluation Mission. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2015)
This paper discusses the key findings of the report on statistics technical assistance (TA) and training evaluation mission on Guatemala. It is observed that overall users trust macroeconomic statistics in Guatemala. Data-producing agencies viewed TA and training provided by Statistics Department, IMF during 1998-2015 as most effective to improving the quality of statistics. There is broad recognition of the Bank of Guatemala's key role in producing and disseminating statistics. There was consensus that TA and training were effective and helped enhance data quality of all datasets, but to a modest extent Government Finance Statistics and Producer Price Index. The effectiveness of TA largely depends on capacity built in the main data-producing agencies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet